Oral health‐related quality of life in patients with disorders of nutrition. (26th December 2018) - Shay, Boaz; Ben Ami, Orly; Levy Ianculovici, Dana; Zini, Avraham; Ianculovici, Clariel; Almoznino, Galit
Summary: Background: Researchers demonstrated a correlation between nutrition and health‐related quality of life (HRQoL). Little is known about the correlation between disorders of nutrition (DON) and Oral HRQoL (OHRQoL). Objectives: (a) To measure OHRQoL in DON patients compared to patients attending nutritional counselling for other reasons (eg, systemic diseases or general dietary counselling) (NCOR) and to healthy controls attending routine dental screenings. (b) To analyse associations between OHRQoL and demographics, health‐related behaviours and nutritional practices. We hypothesised that OHRQoL is impaired in DON patients and correlates with poor health‐related behaviours and nutritional practices Methods: Demographic, smoking, alcohol and physical activity habits, verbal pain scale, oral health impact profile‐14 (OHIP‐14) and nutritional practice data were collected from 63 DON, 35 NCOR and 100 controls. Results: Compared to controls, DON patients exhibited poorer OHIP‐14 global scores and had more functional limitation, physical disability, psychological disability, social disability and handicap. OHIP‐14 global score was positively associated with maternal origin, oral symptoms, eggs and eggplant consumption, avoiding seasoning, hot drinks and fibrous food and negatively associated with physical activity and fresh vegetable consumption. In the conceptual hierarchical multiple regression model, verbal pain scale, eggplant consumption and physical activity were mediators in the relationship between DON and OHIP‐14. DON, physical activity and eggplant consumption also directly associated with OHRQoL. Conclusions: Oral HRQoL was impaired in DON patients and correlated with poor health‐related behaviours and nutritional practices. Routine workup of DON patients should include OHRQoL assessment.